Internalization of Mastery Goals: The Differential Effect of Teachers’ Autonomy Support and Control - Benita, Moti; Matos, Lennia (Frontiers in Psychology, 2021)
Two linked studies explored whether students’ perceptions differentiate between teachers’ autonomy support and control when presenting mastery goals, and the outcomes of these two practices, in terms of students’ internalization of mastery goals and their behavioral engagement. In two phases, Study 1 (N = 317) sought to validate a new instrument assessing students’ perceptions of teachers’ autonomy support and control when presenting mastery goals. Study 2 (N = 1331) demonstrated that at both within and between-classroom levels, perceptions of teachers’ autonomy support for mastery goals were related to students’ mastery goals’ endorsement and behavioral engagement. These relations were mediated by students’ autonomous reasons to pursue learning activities. Perceptions of teachers’ control predicted disengagement through controlled reasons for learning, but only at the within-classroom level. This research joins a growing body of work demonstrating that combining achievement goal theory with SDT can further our understanding of the underpinnings of achievement motivation. It suggests that if teachers want their students to endorse mastery goals (and be more engaged), they need to use more autonomy supportive practices and less controlling ones.